2016
DOI: 10.3390/cells5020014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Adaptive Immune Response by the IκB Family Protein Bcl-3

Abstract: Bcl-3 is a member of the IκB family of proteins and an important regulator of Nuclear Factor (NF)-κB activity. The ability of Bcl-3 to bind and regulate specific NF-κB dimers has been studied in great depth, but its physiological roles in vivo are still not fully understood. It is, however, becoming clear that Bcl-3 is essential for the proper development, survival and activity of adaptive immune cells. Bcl-3 dysregulation can be observed in a number of autoimmune pathologies, and Bcl3-deficient animals are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 105 publications
(167 reference statements)
0
26
0
1
Order By: Relevance
“…Gene NFIL3 is believed to be associated with the function of adaptive immune lines and natural killer cell development (Seillet et al, 2014). Genes EGR1 (Carter et al, 2007), SOX10 (Fufa et al, 2015), and REL (Hayden and Ghosh, 2011;Herrington and Nibbs, 2016) were found to be associated with prereceptormediated differentiation of thymocytes, proliferation and survival of melanocytes and melanogenesis, and key regulation of inducible gene expression in the immune system, respectively. Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Gene NFIL3 is believed to be associated with the function of adaptive immune lines and natural killer cell development (Seillet et al, 2014). Genes EGR1 (Carter et al, 2007), SOX10 (Fufa et al, 2015), and REL (Hayden and Ghosh, 2011;Herrington and Nibbs, 2016) were found to be associated with prereceptormediated differentiation of thymocytes, proliferation and survival of melanocytes and melanogenesis, and key regulation of inducible gene expression in the immune system, respectively. Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The Ikaros family of transcription factors in mice activate lymphoid differentiation (Kim et al, 1999) and in mice, Ikzf2 expression is associated with a block in myeloid lineage differentiation (Park et al, 2019). Bcl3 regulates transcription by associating with NFκB and is important for B-cell proliferative responses and involved in T-helper cell differentiation (reviewed in (Herrington and Nibbs, 2016). The upregulation of these lymphoid program genes in gata2b -/-CD41:GFP low cells together with the forward and side scatter differences suggests a lymphoid bias in gata2b -/-HSPCs.…”
Section: Adult Gata2b -/Phenotypic Hspcs Show Upregulation Of Lymphoimentioning
confidence: 99%
“…In contrast, the powerful pro‐inflammatory gene TNF was one of the 6 transcripts downregulated by EVLP. Several of the most significantly upregulated genes are involved in the regulation of cellular proliferation and apoptosis (eg, BCL3 , CDKN1A , MYC ). Other important functional associations include roles in energy metabolism (eg, ARG2 , HK2 ), tissue remodeling (eg, F3 , SERPINE1 , TIMP1 ), and response to oxidative stress (eg, MT1A , MT2A , SOD2 ).…”
Section: Discussionmentioning
confidence: 99%